2015
DOI: 10.1152/jn.00166.2014
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal premotor cortex: neural correlates of reach target decisions based on a color-location matching rule and conflicting sensory evidence

Abstract: We recorded single-neuron activity in dorsal premotor (PMd) and primary motor cortex (M1) of two monkeys in a reach-target selection task. The monkeys chose between two color-coded potential targets by determining which target's color matched the predominant color of a multicolored checkerboard-like Decision Cue (DC). Different DCs contained differing numbers of colored squares matching each target. The DCs provided evidence about the correct target ranging from unambiguous (one color only) to very ambiguous a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
82
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(96 citation statements)
references
References 128 publications
11
82
3
Order By: Relevance
“…Domains in M1 receive inputs from cingulate motor cortex, SMA, PMC, and PPCr, cerebellar inputs relayed via the motor thalamus and sensory inputs, especially proprioceptive inputs from area 3a, adding further levels of competition to the selection process. The PMC and M1 domains are involved in second and third levels of selection (Coallier et al, 2015), based on the different sources of information, as well as being involved in initiating and guiding the sequences of movements for each type of behavior. Ultimately, M1 domains have the most relevant information, and are the most critical in the selection process.…”
Section: The Organization Of Ppc and Parietal-frontal Sensorimotor Nementioning
confidence: 99%
“…Domains in M1 receive inputs from cingulate motor cortex, SMA, PMC, and PPCr, cerebellar inputs relayed via the motor thalamus and sensory inputs, especially proprioceptive inputs from area 3a, adding further levels of competition to the selection process. The PMC and M1 domains are involved in second and third levels of selection (Coallier et al, 2015), based on the different sources of information, as well as being involved in initiating and guiding the sequences of movements for each type of behavior. Ultimately, M1 domains have the most relevant information, and are the most critical in the selection process.…”
Section: The Organization Of Ppc and Parietal-frontal Sensorimotor Nementioning
confidence: 99%
“…Indeed, although previous decision-making experiments that used visual stimuli revealed an encoding of the stimulus sensory properties (i.e. face vs. house) in the occipital and parietal cortices, around 150ms post-stimulus (Delis et al, 2016; Tu et al, 2017), most of them failed to find sensory-related activity in the premotor cortex (Boussaoud & Wise, 1993; Coallier, Michelet, & Kalaska, 2015; di Pellegrino & Wise, 1991; Nakayama, Yamagata, Tanji, & Hoshi, 2008; Wang et al, 2019). Rather, they showed that the premotor plays a key role in the conversion of sensory information into a choice-related signal (Cisek & Kalaska, 2002; Donner et al, 2009; Wang et al, 2019).…”
Section: Discussionmentioning
confidence: 98%
“…In the last years different groups have addressed the role of PMd in somatomotor decision by employing tasks in which the sensorial instruction required some form of discrimination (establishing which amount of two colours was more present 33,35 ) or could continuously change 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Neural activity of this area represents various properties of the impending movement, including its direction, distance, trajectory, timing and speed 19,20,21,22,23,24,25,26,27,28,29,30,31 , it signals the direction of potential and final reach choices 14 as well the selection of specific rules 32 . Furthermore it reflects conflicts related to the dynamic competition between contemporary alternative movement choices 33,34 , and express a decision process related to the selection of actions based on sensory cues 35 or dynamic sensory signals 34 as well change of mind 36 . Of relevance, PMd contains neural activity that modulates according to movement inhibition 37,38 .…”
Section: Introductionmentioning
confidence: 99%